Effect of Profitability, Business Size, and Institutional Ownership on Business Value with Capital Structure as a Moderating Variable (Empirical Study on Food and Beverage Companies Listed on The Indonesia Stock Exchange for The 2017-2020 Period) - Atwal Arifin; Siti Fauziah; Agus Endro Suwarno (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study is to analyze the effect of profitability, firm size and institutional ownership on firm value with capital structure as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange of the period of 2017 – 2020. The sampling method in this study is purposive sampling, where 48 companies were selected as the sample. The data processing technique in this study uses multiple regression analysis using the IBM SPSS Statistics 25 program. The results of this study show that profitability has an effect on firm value, firm size has no effect on firm value, and institutional ownership has no significant effect on firm value. Capital structure can moderate profitability with firm value, but cannot moderate firm size and institutional ownership.